Incidental extraspinal imaging findings on adult EOS full body radiographs: prevalence and clinical importance - Lily Wood (BMC Medical Imaging, 2021)
Abstract Purpose The purpose of this study was to review our institutional experience with the EOS machine in order to identify the incidence and clinical significance of incidental extraspinal findings (IESF) in an adult spinal deformity population. Methods Our institutional database was queried for all full-length standing radiographs generated by the EOS machine. Dictations were reviewed and the number of incidental extraspinal findings were classified using a previously described system. All findings related to the spine were excluded. A subset of electronic medical records were reviewed to determine further workup for individual findings of suspected clinical significance. Results Original database query based on radiology reports returned a total of 1857 EOS studies. Duplicate studies, studies without the entire body, and patients with more than 1 study during the search period were excluded. 503 patient studies (55.5% female, mean age 59-years-old, range 18 to 91-years-old) met inclusion criteria. The overall rate of incidental extraspinal findings in our study was 60.4% (304 findings in 503 patients). Most findings were classified as Minor. The rate of Major and Moderate findings was 4.8%. The final rate of clinically significant incidental extraspinal findings was 0.8% and included 3 presumed metastatic lesions in long bones and 1 pulmonary nodule. Conclusion To our knowledge this is the first study that reports the rate of incidental extraspinal findings on full body EOS studies. We report a low rate (0.8%) of clinically significant incidental extraspinal findings which is lower than that of CT or MRI. Further research is warranted in comparing EOS and standard radiography.